On the thinking of development trend of chronic disease management in the elderly (新形势下老年慢病管理发展趋势的思考) - YANG Mei (杨梅) (Association of Integrative Nursing, 2023)
The paper expounds the connotation and development trend of chronic disease management in the elderly, discusses the current situation and challenges of chronic disease management in the elderly from five dimensions of precision medicine, symptom management, concept management of "wisdom", integration of diversified management and comprehensive intervention of Traditional Chinese Medicine, and analyzes the management countermeasures. (本文阐述了老年慢病管理的内涵、发展趋势, 从精准医学、症状管理、"智谋"概念管理、多元化管理融合、中医综合干预五个维度探讨了老年慢病管理现状与面临的挑战, 并分析了管理对策, 旨在为老年慢性病健康问题提出切实可行的解决方案。)